Changes in plant nitrogen acquisition strategies during the restoration of spruce plantations on the eastern Tibetan Plateau, China. (April 2018) - Zhang, Ziliang; Li, Na; Xiao, Juan; Zhao, Chunzhang; Zou, Tingting; Li, Dandan; Liu, Qing; Yin, Huajun
Abstract: Despite the importance of plant nitrogen (N) acquisition strategies for plant growth and the structure and functioning of ecosystems, few studies have investigated the N acquisition preference of plants and their reliance on various N sources (nitrate (NO3 − ), ammonium (NH4 + ), and organic N (DON) in soil) during different stages of plantation restoration caused by land-use change. In this study, we used the isotopic mass-balance methods to quantitatively estimate the contributions of N sources (NO3 − vs. NH4 + vs. DON) and plant N preferences in spruce ( Picea asperata Mast.) plantations of different ages (i.e., 20, 30, 40, 50, and 70 years old) on the eastern Tibetan Plateau, China. Across all restoration stages, while plants in spruce plantations preferred soil inorganic N over soil DON, soil DON was a notable N contributor to plant N nutrition, with 23%–44% of plant N derived from DON. Moreover, with the development of plantation restoration, the N source preferences of plants switched from NO3 − (i.e., 20- and 30-yr-old plantations) to NH4 + (age of plantations ≥ 40 years old). Our results suggest that soil DON can be an important N source in alpine coniferous forests. In addition, the shift in the dominant N source during plantation restoration may manifest a strategic adjustment of plant N acquisition in response to changes in soil N availability and/or physiological traits. Highlights: We used the isotopic mass-balance method to quantify contributions of nitrogen (N) sources to plants. DON is an important source in alpine coniferous forests on the eastern Tibetan Plateau, China. Plants can modify N acquisition preferences along plantation restoration gradients. Soil N availability and/or plant physiological traits impact plant N strategies.